Published Privacy Rights via Short Messages - Syahril, Muhammad Akbar Fhad (Amsir Law Journal, 2021)
Short messages in the form of advertisements are increasingly being accepted by the public through their cell phones. The public never specifically gave the phone number to the party sending the advertising message. This is considered to be even more annoying because the short message advertisement violates the principles of consumer protection. This study aims to determine and analyze the extent of privacy violations against the spread of spam information via short messages. This study uses the empirical normative method, namely research conducted with the approach of legal norms or substances, legal principles, legal postulates, and legal comparisons, using a conceptual approach. The results show that short messages in the form of offers that are not directly related to the services used by cellular subscribers must be a concern for customer convenience.